Análisis de caso de artritis séptica con enfoque infantil y el proceso de atención de enfermería. - Calderón Riofrio, Nicole Brigitte (2018)
Septic arthritis is an infection produced in the joints caused by the virus, adults over 80 years and children under 5 years, the socioeconomic level influences the appearance of this disease, the treatment is clinical surgical, the duration depends on the etiological agent that causes the infection. The objective of interest with the present work is to analyze a clinical case of childhood septic arthritis in an 8-year-old child, through the documentary review of the clinical history with specific purposes in patients with chronic disease in patients suffering from this pathology. The exhaustive review of scientific articles, of the clinical history, through the matrix of information collection, the summary of the bibliographic researches, the fundamental antecedents in the behind of the investigation, which allows the precision and the precision of our knowledge of the study. The current state of the pathology, the selection of legal ethical data, the request of Teófilo Dávila Hospital to have access to the permission of the clinical history, the documentary review of the clinical history and the realization of the data collection matrix, the modality of research in Qualitative, which is based on the observation of the clinical characteristics of the case to be studied, describes the depth of our object of study, our method of study which is already the main one of our study is the human being Results were obtained from the patient's clinical history, using categorization systems in data analysis such as; anamnesis, vital signs, personal antecedents, familiar antecedents, current state, diagnosis, complementary examinations, treatment and actions of nursing, obtaining in this way a matrix and locating the data according to the categories previously presented. Some authors emphasize that childhood septic arthritis is an inflammatory process of a joint, which is the cause of the presence of several infectious agents, being the most common Staphylococcus aureus, is a problem of great importance that does not have a great literary openness within the field of health, there are some registered cases of which none presents the interventions made by the part of the personnel that complies with the care, this disease is common in pediatric patients, which is why the work is intended to contribute of quality for the participation of nursing professionals, is proposed through a case study of nursing actions or interventions that must be performed to improve the patient's hospital stay based on the needs identified in the objective data and the subjects identified in the present investigation, the risk factors of arthritis I know children's optics are aimed at the four components present in the theory of the health fields of Lalonde, the most relevant component in our case study is human biology that wants to know that a pediatric patient keeps his immune system adequate not to attribute the risk for the existence of an infection, which did not happen with the patient of our case study in which it was confirmed by the results of the laboratory tests.